Assessing knowledge and awareness about syphilis among undergraduate students in the faculty of engineering at Mangosuthu University of Technology (MUT). - Thwala, Sanelisiwe Portia; S. Shangase (Student’s Journal of Health Research Africa, 2025)
Background Syphilis is a genital ulcerative condition caused by the bacterium called Treponema pallidum. It can cause multiple organ and system failure, which can lead to death if left untreated. The main risk factors of syphilis transmission are inconsistent condom use, having several sex partners, and sharing needles during injection of medication. Syphilis is emerging as a public health problem in sexually transmitted Infections, and research has shown a rise in infections among adults at KwaZulu-Natal universities. Aim and Objective: This research aimed to assess the knowledge and awareness of syphilis among undergraduate students in the Faculty of Engineering at MUT, and the objective was to evaluate the incidence of syphilis infection among male and female students in the Faculty. Methodology This study was conducted at MUT, targeting a population of 210 undergraduate students in the Faculty of Engineering. The data was collected by use of an online survey using Google Forms, and responses were imported to an Excel spreadsheet. Research findings The results showed 44% of the study participants had basic awareness of syphilis infection, 40% had advanced knowledge, and 16% had no understanding of syphilis. Females were shown to have higher levels of awareness and knowledge about syphilis infection (55% vs. 45% for males). 85% of the study participants had never been exposed to syphilis, 11% had been previously infected, and 4% had no known exposure. Conclusion Most MUT engineering undergraduate students know of the existence of syphilis infection; however, there is still a need to do more awareness campaigns. Recommendations Health Education Programs and Modules: Incorporating sexual health education, including information on syphilis and STIs, into academic curricula or general university modules makes health education programs compulsory.